Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Pertumbuhan Ekonomi di Kota dalam Wilayah Jawa Timur (Tahun 2010-2019) - Arif Hartadi (Diponegoro Journal of Economics, 2022)
This research aimed to find how the effect of Local Revenue and Fiscal Balance Transfer on Economic Growth of 9 cities in East Java Province from 2010-2019. The data used secondary data which collected from Statistic Indonesia (BPS) of East Java Province. The method of collecting samples in this study using purposive sampling technique. The method used in this study is multiple linear regression analysis. The result of this research showed that both Local Revenue and Fiscal Balance Transfer simultaneously influenced on Economic Growth. Partially, the Local Revenue has negative and significantly affects on Economic Growth. For the last result, the Fiscal Balance Transfer has positive and significantly affects on Economic Growth.